1990
DOI: 10.2113/gsecongeo.85.3.482
|View full text |Cite
|
Sign up to set email alerts
|

Geology of the Almaden mercury deposit, Province of Ciudad Real, Spain

Abstract: Almadan is the largest known mercury deposit in the world. It is formed by three lenticular strata-bound cinnabar impregnations in the two quartzite members of the Criadero quartzite formation of Lower Silurian age, adjacent to a lens of a phreatomagmatic explosion breccia (Frailesca) filling a crater piercing this quartzite. Cinnabar is the dominant ore mineral, with some native mercury, pyrite, and subordinate, late metacinnabar. The underlying, the intercalated, and the overlying shales (positioned with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…One of the largest natural sources of mercury in the world is located at cinnabar mines near Almadén, Spain 31 32 33 , approximately 300 km ENE of Perdigões ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the largest natural sources of mercury in the world is located at cinnabar mines near Almadén, Spain 31 32 33 , approximately 300 km ENE of Perdigões ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This area corresponds to the biggest mercury geochemical anomaly in the world and has yielded almost one third of the total global production of this element (Hernández et al, 1999). Descriptions of the geological characteristics of the area can be found in reports by Saupé (1990) and Hernández et al (1999), among others, while Lindberg et al (1979), Huckabee et al (1983), Higueras et al (2003), Millán et al (2004Millán et al ( , 2006Millán et al ( , 2011, Molina et al (2006), Moreno-Jiménez et al (2006), Martínez-Coronado et al (2011) have described environmental concerns regarding mercury in the area and include local soil/plant relationships. In particular, Molina et al (2006) reported mercury contents in olive tree leaves, which is the main aspect discussed in this paper.…”
Section: The Study Areamentioning
confidence: 99%
“…On the other hand, Asturias has a more complex mineralization, with high proportions of arsenic in its paragenesis. It is important to highlight that Almadé n is the largest cinnabar (HgS) deposit in the world and it has been active since the Roman times until the present days, having accounted for about one third of the total Hg world production (Herná ndez et al, 1999;Saupé, 1990). Metallurgical processing in the study area evolved from Bustamante furnaces, with roasting temperatures over 873 K, to Pacific furnaces in the last century, reaching temperatures of up to 1073 K.…”
Section: Study Sitesmentioning
confidence: 99%